BORDERLINE AND CLASSIFICATION IN THE COMMUNITY REGULATORY FRAMEWORK FOR MEDICAL DEVICES - BRIEF REVIEW ON SOME DENTISTRY PRODUCTS. - Maya Lyapina; Mariela Yaneva-Deliverska; Jordan Deliversky; Angelina Kisselova (Peytchinski Publishing, 2015)
Defining a given product as a medical device and interpretation of the application of the classification rules fall within the competence of the competent authorities of the Member States where the product is on the market. Different interpretations of Community legislation occur, and, can put public health at risk and distort the internal market. Borderline cases are considered to be those cases where it is not clear from the outset whether a given product is a medical device, an in vitro diagnostic medical device, an active implantable medical device or not. Classification cases can be described as those cases where there exists a difficulty in the uniform application of the classification rules as laid down in the Medical Devices Directive (MDD), or where for a given device, depending on interpretation of the rules, different classifications can occur. The aim of the present work is to make a brief review on discussion on classification in the community regulatory framework for medical devices of some dentistry products.